The Aristocratic Poet: Juan Ramón Jiménez’s Reading of Walt Whitman - Rodríguez Guerrero-Strachan, Santiago (Complutense Journal of English Studies, 2019)
The essay analyses Juan Ramón Jiménez’s reading of Walt Whitman as an aristocrat. For Jiménez, aristocracy is not a term associated with nobility. Instead, it is related to the intellectual effort that a poet – or any person – makes to improve himself, while at the same time maintaining ties with the folk. Jiménez wrote on Whitman in Alerta and El Modernismo. Apuntes de un curso and mentioned him in other essays and lectures. For Jiménez who used the American poet to foreground his own poetics, Whitman stood as one of the precursors of Spanish and Spanish American modernismo. Jiménez’s preference for the folk, led him to assert that he preferred Whitman’s brief poems to his big epic poetry which was then and continues to be the readers’ favourite.